Pengaruh Penambahan Rgo Pada Lafeo3 Yang Didoping Co Terhadap Energi Adsorpsi Molekul Etanol Menggunakan Density Functional Theory Untuk Sensor Gas - Alta Ridho Anugrah; Andhy Setiawan; Yuyu Rachmat Tayubi; Ahmad Aminudin; Lilik Hasanah; Siti Kudnie Sahari; Endi Suhendi (Universitas Pendidikan Indonesia, 2023)
LaFeO3 (LFO) material has been widely used as a gas sensor construction material. Although LFO has been widely applied to gas sensors, the selectivity and sensitivity as well as the working temperature of gas sensors are still not optimal. In this study, the LFO was Co-doped and coated with single layer rGO to analyze its sensitivity and selectivity based on adsorption energy using Density Functional Theory (DFT). Based on this research, it was found that the presence of Co doping and rGO coating could increase the adsorption energy on the LFO. The addition of the rGO layer to the LFO increased the adsorption energy by 23.58% from -2.38 eV for Co-doped LFO to -2.93 eV when rGO was added. This shows the potential of adding rGO layers to LFO materials for sensor materials.